The Sociology of Space and Its Pioneers - Ahmadin, Mr. (Jurnal Kajian Sosial dan Budaya: Tebar Science, 2025)
The sociology of space has so far made important contributions to the development of social theories, especially the study of urban society, public space, and urban planning. This paper discusses some of the pioneers of the sociology of space, the social reality in which they live that influences their spatial imagination, and their written works. This type of research is a literature review in the form of tracing sources through the review of books, articles, and other types of scientific works. The results showed that there are several people who are famous as pioneers of this type of sociology, namely: Georg Simmel, Michael Foucault, Henri Lefebvre, David Harvey, Manuel Castells, Edward Soja, Martina Low, and Doreen Massey. Each of these pioneers, either separately or together, gave a distinctive color to the study of sociology using the auxiliary sciences of geography and architecture. The discussion of the pioneering figures of the sociology of space will also facilitate readers in the theoretical categorization process of who influenced what figures and was influenced by whose figures as “narrators”.